Sosialisasi Penyelesaian Masalah Klaim Penanganan Medical Logistik (Vaksin) melalui Ground Handling Bandara Soekarno Hatta - Lis Lesmini; Wynd Rizaldy; Muhammad Iqbal Firdaus (Institut Transportasi dan Logistik Trisakti, 2022)
The purpose of this activity is to provide socialization of problem solving of claiming medical logistics (Vaccine) handling to companies that handle medical logistics (vaccines) where most of the vaccines are included in the S oekarno Hatta ground handling warehousing, so that they can have human resources who understand and understand about handling medical logistics (vaccine) damage claims in accordance with the Regulations handling of international Air Transport Association (IATA) claims regarding Temperature Control Regulation and also The Air Cargo Tariff, so as to improve services to customers and assist government programs in overcoming the Covid 19 Pandemic. The activity was held on March 2, 2022 in Tangerang. Themethod used is socialization through online and offline with materialmapping, question and answer and video playback. Participants 13 people consisting of employees of various companies that handle medical logistics (vaccines) at Soekarno Hatta Airport, based on the results of the pre-survey and post survey given to participants, it shows an increase in participants' understanding and knowledge by 62.4% related to procedures for handling damage claims medical logistics (vaccines) and a good response of 61.54% from the participants that this socialization is useful and can be directly applied to their work and meet the target of achieving the PKM plan. This activity has been published through the Youtube channel so that it can be seen and studied by the wider community.